Casitas B-lineage lymphoma linker helix mutations found in myeloproliferative neoplasms affect conformation. Issue 1 (December 2016) - Buetow, Lori; Tria, Giancarlo; Ahmed, Syed; Hock, Andreas; Dou, Hao; Sibbet, Gary; Svergun, Dmitri; Huang, Danny
Abstract Background Casitas B-lineage lymphoma (Cbl or c-Cbl) is a RING ubiquitin ligase that negatively regulates protein tyrosine kinase (PTK) signalling. Phosphorylation of a conserved residue (Tyr371) on the linker helix region (LHR) between the substrate-binding and RING domains is required to ubiquitinate PTKs, thereby flagging them for degradation. This conserved Tyr is a mutational hotspot in myeloproliferative neoplasms. Previous studies have revealed that select point mutations in Tyr371 can potentiate transformation in cells and mice but not all possible mutations do so. To trigger oncogenic potential, Cbl Tyr371 mutants must perturb the LHR-substrate-binding domain interaction and eliminate PTK ubiquitination. Although structures of native and pTyr371-Cbl are available, they do not reveal how Tyr371 mutations affect Cbl's conformation. Here, we investigate how Tyr371 mutations affect Cbl's conformation in solution and how this relates to Cbl's ability to potentiate transformation in cells. Results To explore how Tyr371 mutations affect Cbl's properties, we used surface plasmon resonance to measure Cbl mutant binding affinities for E2 conjugated with ubiquitin (E2–Ub), small angle X-ray scattering studies to investigate Cbl mutant conformation in solution and focus formation assays to assay Cbl mutant transformation potential in cells. Cbl Tyr371 mutants enhance E2–Ub binding and cause Cbl to adopt extended conformations in solution. LHR flexibility, RING domain accessibility and transformation potential are associated with the extent of LHR-substrate-binding domain perturbation affected by the chemical nature of the mutation. More disruptive mutants like Cbl Y371D or Y371S are more extended and the RING domain is more accessible, whereas Cbl Y371F mimics native Cbl in solution. Correspondingly, the only Tyr371 mutants that potentiate transformation in cells are those that perturb the LHR-substrate-binding domain interaction. Conclusions c-Cbl's LHR mutations are only oncogenic when they disrupt the native state and fail to ubiquitinate PTKs. These findings provide new insights into how LHR mutations deregulate c-Cbl.